عروج امت کی نظریاتی و عملی جہات: قرآنی تصور اور منتخب اہل علم کی آراء کا تجزیاتی مطالعہ : Theoretical and Pragmatical Aspects of the Rise of Muslim Ummah: A Theoretical Examination of Quranic Concept and Analytical Study of Selected Scholars’ Views - Umer Yousaf; Dr. Farhana Mehmood (MEI, 2024)
This article delves into the theoretical and pragmatic dimensions surrounding the rise of the Muslim Ummah, combining a theoretical exploration of Quranic concepts with an analytical study of perspectives offered by eminent scholars. Drawing upon the rich tapestry of Quranic teachings, the study seeks to unravel the conceptual underpinnings of the Ummah's ascent. Additionally, it conducts a thorough analysis of the views articulated by select scholars, providing insights into their interpretations and implications for practical application Central to this examination is an exploration of Quranic verses that elucidate the principles and dynamics underlying the rise of the Muslim community. These verses serve as foundational pillars upon which subsequent theoretical frameworks are constructed, guiding our understanding of the Ummah's historical trajectory and potential for future development. Moreover, the study scrutinizes the interpretations of esteemed scholars, synthesizing their perspectives to offer a comprehensive view of the subject matter. Key themes explored include the role of faith, unity, societal organization, and divine guidance in shaping the trajectory of the Muslim Ummah. Theoretical frameworks are complemented by pragmatic considerations, with insights gleaned from the analyses of scholars offering guidance on how these principles may be applied in contemporary contexts.